2000
DOI: 10.1002/1097-0096(200009)28:7<347::aid-jcu5>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Relative risk of cancer in sonographically detected thyroid nodules with calcifications

Abstract: Purpose The aim of this prospective study was to evaluate the significance of sonographically detected thyroid calcifications in the diagnosis of thyroid cancer. Methods One hundred eighty‐eight patients with thyroid disease, including 37 with thyroid cancer, were included in the study. Each patient underwent preoperative, high‐resolution sonography to evaluate the thyroid gland for the presence of calcifications. Results The highest incidence of calcification was found in thyroid cancer (54%), followed by mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0
7

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 25 publications
6
35
0
7
Order By: Relevance
“…Compared to the non-calcified MNG, the calcified solitary nodule was associated with a relative risk of cancer of 22.8 (95% CI, 5.4-95.5). [44]. Another study found among patients with solitary nodules, a frequency of 75.7% of DTC, when ultrasonography had shown microcalcifications [45].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the non-calcified MNG, the calcified solitary nodule was associated with a relative risk of cancer of 22.8 (95% CI, 5.4-95.5). [44]. Another study found among patients with solitary nodules, a frequency of 75.7% of DTC, when ultrasonography had shown microcalcifications [45].…”
Section: Discussionmentioning
confidence: 99%
“…Leur pré-sence multiplie par 2,5 le risque de cancer [18]. Ce risque atteindrait 75 % pour les nodules solitaires [19].…”
Section: Les Calcificationsunclassified
“…Or, la spécificité des calcifications dépend de l'âge du patient et du nombre de nodules. En effet, la fréquence des calcifications augmente avec l'âge [18], l'âge moyen des sujets ayant des nodules calcifiés est de 55 ans, versus 43 ans pour les sujets sans nodule calcifié. Le risque de cancer est donc plus élevé chez les sujets jeunes avec nodules calcifiés : 87 % de carcinomes avant 40 ans, vs 57 % après [18].…”
Section: Les Calcificationsunclassified
See 2 more Smart Citations